2015
DOI: 10.16986/huje.2015014664
|View full text |Cite
|
Sign up to set email alerts
|

Reflections from Pre-Service Teachers Mathematics Teaching Process

Abstract: Pedagogical Content Knowledge (PCK) has been considered to be the most important factor for identifying the role of the teacher in carrying out effective teaching. This paper examines, with respect to the components of PCK, the types of difficulties that a group of pre-service teachers encountered during the process of designing teaching activities. For this purpose, 8 pre-service teachers (4 elementary mathematics and 4 classroom teachers) are observed whilst teaching mathematics during the Teaching Practicum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 26 publications
0
5
0
2
Order By: Relevance
“…This is a professional development model which enables participants to see the in-class implementations from a different perspective (Stigler & Hiebert, 1999), and it is also identified as "a collaborative professional development approach for teachers" (Murata, 2011;Lewis & Tsuchida, 1998;Stigler & Hiebert, 1999). This approach includes the stages in which the teachers come together and then plan, apply, and evaluate an efficient lesson collaboratively, which will enable the students to learn (Murata, 2011;Baki, Baki & Arslan, 2011). Among the educational survey models, the "lesson study" model, which is a qualitative research method, was used in this research with the aim of developing the geometric thinking levels of secondary school teachers in their own school environments.…”
Section: Methodsmentioning
confidence: 99%
“…This is a professional development model which enables participants to see the in-class implementations from a different perspective (Stigler & Hiebert, 1999), and it is also identified as "a collaborative professional development approach for teachers" (Murata, 2011;Lewis & Tsuchida, 1998;Stigler & Hiebert, 1999). This approach includes the stages in which the teachers come together and then plan, apply, and evaluate an efficient lesson collaboratively, which will enable the students to learn (Murata, 2011;Baki, Baki & Arslan, 2011). Among the educational survey models, the "lesson study" model, which is a qualitative research method, was used in this research with the aim of developing the geometric thinking levels of secondary school teachers in their own school environments.…”
Section: Methodsmentioning
confidence: 99%
“…Alternatively, it has been established that by constructing dynamic items with augmented reality, students can observe objects from various angles, resulting in active learning (Anggraini et al, 2020). High-level cognitive skills are required for spatial reasoning, so related concepts can be embodied in two-or three-dimensional visuals or objects (Baki, 2000). The relationship between spatial reasoning ability and mathematics achievement is consistent and strengthens over time (Resnick et al, 2019;Resnick et al, 2020).…”
Section: Subcomponents Of Spatial Reasoningmentioning
confidence: 99%
“…The idea of knowledge for teaching was systematically introduced for the first time by Shulman (1986), whose work later inspired other researchers, and the types of knowledge were adapted to various disciplines, such as mathematics, physics, and so on (e.g., Ball, Thames, & Phelps, 2008;Grossman, 1990;Koehler & Mishra, 2009). This type of knowledge concerns the professional knowledge that the teacher should have and comprises pedagogical knowledge and knowledge for teaching, along with content knowledge of the course to be taught (Baki, Baki, & Arslan, 2011). Many educators have indicated that a teacher's professional knowledge is related to student achievement (Metzler & Woessmann, 2012;Selling, Gargia, & Ball, 2016), a claim that has been supported by the findings of Baumert et al (2010), who showed a substantial positive impact of pedagogical content knowledge on student learning.…”
Section: Teacher Characteristicsmentioning
confidence: 99%
“…Ball, Thames, i Phelps, 2008; Grossman, 1990;Koehler i Mishra, 2009). Ova vrsta znanja tiče se prvenstveno profesionalnoga znanja koje učitelj treba posjedovati i obuhvaća pedagoško znanje i znanje o poučavanju te poznavanje gradiva nastavnoga predmeta (Baki, Baki, & Arslan, 2011). Brojni poučavatelji naveli su kako je učiteljevo profesionalno znanje povezano s učeničkim postignućima (Metzler i Woessmann, 2012;Selling, Gargia, i Ball, 2016), a ovu tvrdnju potvrđuju i rezultati istraživanja Baumerta i sur.…”
Section: Učiteljske Osobineunclassified